Ragam Bahasa Pedagang Kaki Lima di Pasar Pangkalpinang, Bangka Belitung: Kajian Sosiolinguistik - Hartati, Lasmi; Liana, Lili (Universitas Muhammadiyah Surabaya, 2025)
Street vendors play a very important role in the local economy and are often a representation of the cultural and linguistic diversity of an area. Thus, studying the variety of languages ​​used by street vendors can provide valuable insight into the social identity and dynamics of the community. Based on the geographical and social context, Bangka Belitung is a province consisting of islands with ethnic, cultural and linguistic diversity. Therefore, this research aims to examine the language variety of street vendors in the Pangkalpinang market, Bangka Belitung. This research is a sociolinguistic study, because it discusses language varieties. This means that this research can increase language vocabulary, especially Indonesian. This research is qualitative research with qualitative descriptive methods. The data source in this research is the variety of languages ​​of street vendors in the Pangkalpinang market. The results of the research show that the variety of languages ​​used by traders and buyers uses regional or everyday languages, although sometimes regional languages ​​are used.